The Role of Financial Situation in the Relationship between Environmental Initiatives and Competitive Priorities of Production Companies in Poland - Barbara Fura (Risks, 2022)
The paper aims to determine the role of the financial situation of production companies in the relationship between their environmental initiatives and their factors of competitiveness. The paper takes advantage of primary and secondary statistical data. The former were gathered using the diagnostic survey method, whereas the latter were obtained from the companies’ financial statements. For the analysis of the primary data, structural modeling was applied. The data from the financial statements served to classify enterprises according to their financial situation. The classification was carried out with the use of Mączyńska’s discriminant model. The main findings highlight that more positive effects of environmental initiatives, such as companies’ increased competitiveness, were observed in cases of enterprises with good financial situations. In addition, a weaker impact of pro-environmental initiatives on the increase in companies’ competitiveness was noted in enterprises in poor financial conditions. The results of this research may be potentially applied in those production companies which build their competitiveness based on activities aiming at the protection of the natural environment. They draw attention to the key factors of the competitiveness of enterprises, which are improved as a result of actions for the protection of the natural environment. The originality of the presented research lies in determining the role of the financial situation in the development of the relationship between environmental actions and company competitiveness.